2012
DOI: 10.1088/0957-4484/23/49/495714
|View full text |Cite
|
Sign up to set email alerts
|

Soft cutting of single-wall carbon nanotubes by low temperature ultrasonication in a mixture of sulfuric and nitric acids

Abstract: To decrease single-wall carbon nanotube (SWCNT) lengths to a value of 100-200 nm, aggressive cutting methods, accompanied by a high loss of starting material, are frequently used. We propose a cutting approach based on low temperature intensive ultrasonication in a mixture of sulfuric and nitric acids. The method is nondestructive with a yield close to 100%. It was applied to cut nanotubes produced in three different ways: gas-phase catalysis, chemical vapor deposition, and electric-arc-discharge methods. Rama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Most shortening and cutting strategies take place via a progressive introduction of defects/functionalities into the wall structure until a complete cutting is achieved [52,53]. TGA.…”
Section: Resultsmentioning
confidence: 99%
“…Most shortening and cutting strategies take place via a progressive introduction of defects/functionalities into the wall structure until a complete cutting is achieved [52,53]. TGA.…”
Section: Resultsmentioning
confidence: 99%
“…Short-length CNTs were produced by cutting long-length CNTs using the procedure detailed elsewhere [18]. Atomic force microscopy (AFM, Solver P47 PRO, NT-MDT Inc) showed that intensive ultrasonication in an acid mixture (95% H 2 SO 4 and 59% HNO 3 at volume fractions of 8:1, respectively) at low temperature (<8 °C) allowed reducing the CNT length down to 100-300 nm for all kinds of tubes, without a significant change of their diameter distribution or modification of their electronic properties (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These two steps are repeated once at temperature less than 35°C. The resulting suspension is then diluted with water and the SWCNT-COOH nanotubes, collected through 0.2 μm PTFE membrane, washed with water until pH neutral, dried under vacuum for 2h, and the cutting procedure was verified using TEM imagery [15,16].…”
Section: Methodsmentioning
confidence: 99%